Modelling a Trusted Mechanism for Knowledge Sharing - Marius PETRESCU; Delia Mioara POPESCU; Nicoleta SÎRBU (Revista de Management Comparat International, 2010)
Knowledge sharing has been identified as a major focus area for knowledge management. Efforts are made with a view to identify the most effective ways to share knowledge, as a step towards improving organizational performance. In this striving, various factors have been identified as impediments for knowledge sharing, including inadequate organizational structures, sharing unfriendly organizational cultures, and denominational segregation. Related problems may occur when information systems, such as intranets, distributed libraries, document management systems, or groupware applications, are introduced to support knowledge sharing. The extensive use of the IT&C has only added new questions on how to address issues of trust within the present knowledge -rich environment. This paper proposes a new way of approaching knowledge sharing in the context of information and communication technology development. The study provides an overview of the manner and extent in which information assurance concepts of integrity, authenticity, availability, non-repudiation and access-control may be employed to ensure a trusted and effective knowledge sharing process.